Dialogflow Performance Analysis For Learning Services In Learning Management Systems Using Chatbots - Arianto, Yuri; Harijanto, Budi; Asri, Atiqah (International Journal of Frontier Technology and Engineering, 2023)
The variety of smart connection applications continues to increase, and the need for better communication in the network emerges. The conversation application is a solution that users widely use. The one quite popular today is also known as ChatBot. In this study, the implementation of the ChatBot application was applied to the LMS (Learning Management System). The implementation of ChatBot used the ReactJS library technology in creating the user interface. This application could help students learn outside the classroom, especially if they experience difficulties in the learning process. Furthermore, in this study, the Dialogflow technology was tested for matching sentence combinations in the ChatBot application. The tests were carried out on informatics engineering students at the State Polytechnic of Malang in learning Microsoft Office applications. The results of the research experiment resulted in a 100% accuracy value for original sentence questions from the database and 72% accuracy-free questions, for usability testing produces a calculation value of 88.97%. From the results, it could be concluded that it was very feasible and met the criteria in the usability aspect.